THE STRUCTURAL AND ELECTRONIC-PROPERTIES OF THE RU(V) PEROVSKITES BA2LARU0.5SB0.5O6 AND BA2TARU0.5NA0.5O6 - Almaer, S; Battle, P; Lightfoot, P; Mellen, R; Powell, A (1993)
The compounds Ba2LaRu0.5Sb0.5O6 and Ba2TaRu0.5Na0.5O6 have been used to study the magnetic properties of Ru(V) when present in low concentrations in a mixed metal oxide. Ba2TaRu0.5Na0.5O6 is a simple cubic perovskite (a0 = 4.1321(5) Å) with a random distribution of Ta, Ru, and Na over the six-coordinate sites and a magnetic susceptibility that follows the Curie-Weiss Law (μeff 3.44 μB, θ = - 142 K). Neutron powder diffraction has been used to show that Ba2LaRu0.5Sb0.5O6 is a distorted perovskite (space group 1-1, a = 6.0741(5), b 6.0895(5), c = 8.6124(9) Å, α = 89.93(1), β = 90.39(1), γ = 89.91(1)°) with a 1:1 ordered arrangement of La and Ru/Sb atoms over the six-coordinate sites. Again the magnetic susceptibility follows a Curie-Weiss law (μeff 3.78 μB, θ = -170 K). These results are considered in the light of the magnetic susceptibility of Ba2LaRuO6 (μeff = 4.00 μB, θ = -304 K). © 1993 Academic Press. All rights reserved.